Hepatitis C virus infection in a hematology ward: evidence for nosocomial transmission and impact on hematologic disease outcome - E Silini; A Locasciulli; L Santoleri; L Gargantini; G Pinzello; M Montillo; L Foti; A Lisa; N Orfeo; E Magliano; A Nosari; E Morra (Haematologica, 2002)
BACKGROUND AND OBJECTIVES: Hepatitis C virus (HCV) infection is frequent among patients with hematologic malignancies and unapparent routes of infection may be important in this setting. Moreover, the impact of this infection on the outcome of the hematologic disease needs to be better defined. DESIGN AND METHODS: To define sources and clinical courses of HCV infection, an epidemiologic study was performed on 13 patients newly admitted over one year who showed transaminase elevation and anti-HCV seroconversion. The investigation, started in August 1998, included laboratory tests and molecular analysis of virus isolates, and was extended to staff and blood donors. Clinical, hematologic and serologic surveillance of all infected patients were part of the subsequent follow-up study which started in September 1998 and was completed in December 2001. RESULTS: Anti-HCV seroconversion was observed in 13 of 294 patients (4.4%), admitted to the unit from August 1997 and August 1998; 11 of the seroconverted cases had central catheters, 12 received transfusions. Transmission via blood derivatives and staff was ruled out. All patients were infected by genotype 1b and 11 harbored the same viral variant. HCV infection did not influence the course of the underlying disease or the use of specific therapies. Forty months after the outbreak, five patients are alive (one after autologous and one after allogeneic stem cell transplantation), while eight have died, seven of hematologic disease, and one of cardiac failure. None died of liver disease. INTERPRETATION AND CONCLUSIONS: The molecular data suggest a patient-to-patient nosocomial HCV transmission. After having analyzed all the possible routes of transmission, a series of preventive measures were adopted: search for HCV RNA in newly admitted patients, protection of mucosae and isolation of patients during neutropenic phases, and avoidance of multidose vials. As regards the impact of HCV infection on the outcome of the hematologic diseases, changes in the scheduled therapy, including stem cell transplantation, were not required.